2014
DOI: 10.1530/jme-14-0030
|View full text |Cite
|
Sign up to set email alerts
|

Revising the role of the androgen receptor in breast cancer

Abstract: Breast cancer (BC) is traditionally viewed as an oestrogen-dependent disease in which the androgen receptor (AR) is inhibitory, counteracting the oncogenic activity of oestrogen receptor a (ERa (ESR1)). Most probably as a result of this crosstalk, the AR has prognostic value in ER-positive disease, with AR positivity reported to correlate with a better prognosis. Activation of the AR pathway has been previously used as a therapeutic strategy to treat BC, but its usage declined following the introduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 82 publications
1
68
0
6
Order By: Relevance
“…Expression of AR is associated with good prognosis in ER+ breast cancer (Hu et al 2011, Hilborn et al 2016, with anti-estrogenic and anti-proliferative effects in ER+ breast cancer being reported (Peters et al 2009. The anti-proliferative effect of AR is partly attributed to its inhibitory effect on ESR1 signaling in ER+ breast cancer cells (Peters et al 2009, Fioretti et al 2014. However, AR has also been reported to contribute to therapy resistance in ER+ breast cancer cells overexpressing AR, with increase in AR-to-ESR1 ratio associated with worse outcome for tamoxifen-treated patients (Cochrane et al 2014) and increased agonist activity of Tam in AR overexpressing cells.…”
Section: Nr Expression In Breast Cancer Subtypesmentioning
confidence: 99%
“…Expression of AR is associated with good prognosis in ER+ breast cancer (Hu et al 2011, Hilborn et al 2016, with anti-estrogenic and anti-proliferative effects in ER+ breast cancer being reported (Peters et al 2009. The anti-proliferative effect of AR is partly attributed to its inhibitory effect on ESR1 signaling in ER+ breast cancer cells (Peters et al 2009, Fioretti et al 2014. However, AR has also been reported to contribute to therapy resistance in ER+ breast cancer cells overexpressing AR, with increase in AR-to-ESR1 ratio associated with worse outcome for tamoxifen-treated patients (Cochrane et al 2014) and increased agonist activity of Tam in AR overexpressing cells.…”
Section: Nr Expression In Breast Cancer Subtypesmentioning
confidence: 99%
“…The signaling effect of AR depends on its interaction with ER signaling (Chia et al 2015) because a cross talk exists between these two receptors (Fioretti et al 2014).…”
Section: Figurementioning
confidence: 99%
“…AR expression in breast cancer is associated with an increase in cell proliferation through AR signalling [14]. However, the correlation between AR expression and prognosis remains unclear, because of conflicting reports regarding the influence of AR on tumor progression [7,11,15]. Henley et al suggested that the lack of AR expression may play a critical role in the transformation of high-grade ductal carcinoma in situ (HG-DCIS) to high-grade invasive ductal carcinoma (HG-IDC) [16].…”
Section: Introductionmentioning
confidence: 99%